The Information Content of Stock Dividend Announcements. - Foster III, Taylor W.; Vickrey, Don (The Accounting Review, 1978)
Abstract The primary goals of this paper were (a) to test the information content of stock dividend announcements and (b) to produce evidence about the validity of the AICPA conclusion that small stock dividends almost always produce significant amounts of extra value on the ex date and that large stock dividends fail to generate such ex date value. In regard to the first objective, the authors' findings imply that the market, in the aggregate, uses stock dividend information in setting equilibrium security prices, that much of the market's reaction to such information occurs no later than the declaration date, and that such information tends to produce positive unexpected returns. With respect to the second goal, the results imply that the market is not conditioned to react positively to stock dividends of any size on the ex date and, consequently, that the AICPA conclusion is valid (invalid) with respect to large (small) stock dividends.